'There Are Voices in Every Direction': Organizational Decoupling in Frontex*. (29th July 2019) - Perkowski, Nina
Abstract: This article analyses Frontex through the lens of organizational sociology, challenging conventional accounts of the agency as a coherent, rational actor. Drawing on interviews and ethnographic fieldwork, it argues that Frontex can more appropriately be understood as a fragmented and only loosely coupled organization, with discrepancies existing between different units, languages and structures, and between those implementing Frontex operations on the ground, staff in the headquarters, and the management board. The article shows that, faced with contradictory demands, Frontex seeks to maintain support from its environment and to preserve legitimacy among its key stakeholders; in particular the European Parliament, the Commission and different member states. The loose coupling of the agency allows for the coexistence of different rationalities across different aspects of Frontex's work, catering to diverse stakeholders while also minimizing open conflict within the organization.